Bản so sánh quy định của Nghị quyết số 85/2014/QH13 ngày 28/11/2014 của Quốc hội với dự thảo Nghị quyết sửa đổi, bổ sung Nghị quyết số 85/2014/QH13 ngày 28/11/2014 của Quốc hội - Quốc hội Khoá XV (2023)
Toàn văn Bản so sánh quy định của Nghị quyết số 85/2014/QH13 ngày 28/11/2014 của Quốc hội với dự thảo Nghị quyết sửa đổi, bổ sung Nghị quyết số 85/2014/qh13 ngày 28/11/2014 của Quốc hội.